Paleogene post-collisional forearc evolution of the Northern Andes revealed by U-Th-Pb detrital zircon geochronology and Lu-Hf systematics, in the Cauca Basin, Colombia - S. Zapata; G.E. Botello; A. Cardona; L. Calderon-Diaz; S. Echeverri; M. Carvalho; H.D. Arboleda; M. Marulanda; J.S. Jaramillo-Ríos; V. Valencia; A. Pardo-Trujillo (Journal of South American Earth Sciences, 2026)

Late Miocene – Pliocene eastward magmatic arc migration record in the Northern Andes at 5°N latitude, west-central Colombia - Sebastián Echeverri; Hugo Murcia; Eliana Botello; Juan C. Valencia-Gómez; Agustín Cardona; Sebastián Rosero; Luis A. Botero-Gómez; Victor Valencia (International Geology Review, 2026)

Species richness and ecological connectivity of the mammal communities in urban and peri-urban areas at Mexico City - Pablo César Hernández Romero; Juan J. Von Thaden Ugalde; Carlos E. Muench; Diego Magaña Rodríguez; María del Coro Arizmendi; Francisco Botello; David A. Prieto-Torres (Urban Ecosystems, 2024)
Urban expansion has emerged as a pervasive driver of biodiversity loss in Mexican cities due to shifts in landscape composition and configuration. Hence, the preservation of forest cover, green spaces and isolated trees assume a critical role in conserving the biodiversity within urban areas. We compared mammal assemblages across 520 sites in Mexico City examining the impact of local vegetation and site characteristics (e.g., patch size, isolation distance) on diversity patterns. Then, we used a generalized linear model to evaluate the relationship between mammal assemblages (including both alpha and beta diversities) and the level of structural and functional connectivity across the landscape. We collected 5,063 records of 38 species from the sampled sites. Mammalian richness ranged from 1 to 9 spp./site, and the mean of taxonomic and functional (Functional Distance [MFD]) alpha diversities were 1.9 ± 1.3 spp./site and 0.41 ± 0.60 MFD/site, respectively. The average size of habitat fragments was 0.41 hectares, and the percent forest cover per site ranged from 0.5 to 100%. Both species and functional alpha diversities were different among the land-use and vegetation types (including protected vs . non-protected areas). There was a clear distinction (β value > 0.40) in species composition across the landscape, which was positively related to geographical distance and negatively related to connectivity between sites. We identified four main patches especially important to connectivity across the city and argue that conserving them is critical for restoring key components of biodiversity and ecosystem services in urban and peri-urban areas of Mexico City.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Presence of Oil Mineral Aggregates (OMAs) in Surface Sediments from Mexico’s Exclusive Economic Zone, NW Gulf of Mexico - Alfredo Zubillaga; Luis A. Soto; Diana L. Salcedo; Alfonso V. Botello (Bulletin of Environmental Contamination and Toxicology, 2018)

Analysis and Tendencies of Metals and POPs in a Sediment Core from the Alvarado Lagoon System (ALS), Veracruz, Mexico - A. V. Botello; F. S. Villanueva; R. F. Rivera; A. L. Velandia; G. E. de la Lanza (Archives of Environmental Contamination and Toxicology, 2018)

The environmental legacy of the Ixtoc-I oil spill in Campeche Sound, southwestern Gulf of Mexico - Luis A. Soto; Alfonso V. Botello; Sergio Licea-Durán; Marcial L. Lizárraga-Partida; Alejandro Yáñez-Arancibia (Frontiers in Marine Science, 2014)

Pollution by organochlorine pesticides in Navachiste-Macapule, Sinaloa, Mexico - Adriana M. Montes; Fernando A. González-Farias; Alfonso V. Botello (Environmental Monitoring and Assessment, 2012)

Persistent Organochlorine Pesticides in Coastal Sediments from Petacalco ay, Guerrero, Mexico - D. O. Leyva-Cardoso; G. Ponce-V; A. V. Botello; G. Daz-Gonzlez (Bulletin of Environmental Contamination and Toxicology, 2003)

PAH Levels in Bivalve Mollusks from the Mexican Subtropical Pacific - A. V. Botello; C. García-Ruelas; G. Ponce-Vélez (Bulletin of Environmental Contamination and Toxicology, 2002)

Polycyclic Aromatic Hydrocarbons in Sediments from Coastal Lagoons of Veracruz State, Gulf of Mexico - A. V. Botello; L. G. Calva B; G. Ponce V (Bulletin of Environmental Contamination and Toxicology, 2001)

Persistent Organochlorine Pesticides (POPs) in Coastal Lagoons of the Subtropical Mexican Pacific - A. V. Botello; L. Rueda-Quintana; G. Díaz-González; A. Toledo (Bulletin of Environmental Contamination and Toxicology, 2000)

Polycyclic Aromatic Hydrocarbons in Sediments from Pueblo Viejo, Tamiahua, and Tampamachoco Lagoons in the Southern Gulf of Mexico - A. V. Botello; L. G. Calva B. (Bulletin of Environmental Contamination and Toxicology, 1998)

Acute Toxicity and Synergism of Cadmium and Zinc in White Shrimp, Penaeus setiferus, Juveniles - C. Vanegas; S. Espina; A. V. Botello; S. Villanueva (Bulletin of Environmental Contamination and Toxicology, 1997)